2012
DOI: 10.1165/rcmb.2011-0099oc
|View full text |Cite
|
Sign up to set email alerts
|

Roles for β-Catenin and Doxycycline in the Regulation of Respiratory Epithelial Cell Frequency and Function

Abstract: The expression of b-catenin-dependent genes can be increased through the Cre recombinase (Cre)-mediated elimination of the exon 3-encoded sequence. This mutant b-catenin is termed DE3, and promotes the expression of b-catenin-dependent genes. Our previous study used the DE3 model to demonstrate that persistent b-catenin activity inhibited bronchiolar Clara-to-ciliated cell differentiation. The present study was designed to evaluate the roles of b-catenin in regulating the tracheal progenitor cell hierarchy. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 54 publications
1
17
1
Order By: Relevance
“…These TOPGAL mice have provided a sensitive approach for dissecting the role of the canonical β-catenin pathway in lung development [56], injury [57], and repair [58,54], as well as airway epithelial lineage and stem cell studies [59]. Pharmacological approaches to dissect the contribution of WNTβ-catenin canonical signaling include activation by lithium chloride, a well-known inhibitor of GSK-3β [58], or inhibition by using ICG-001, a selective inhibitor of WNTβ-catenin-dependent transcription [60].…”
Section: Wisp1 and The Wnt Pathwaymentioning
confidence: 99%
“…These TOPGAL mice have provided a sensitive approach for dissecting the role of the canonical β-catenin pathway in lung development [56], injury [57], and repair [58,54], as well as airway epithelial lineage and stem cell studies [59]. Pharmacological approaches to dissect the contribution of WNTβ-catenin canonical signaling include activation by lithium chloride, a well-known inhibitor of GSK-3β [58], or inhibition by using ICG-001, a selective inhibitor of WNTβ-catenin-dependent transcription [60].…”
Section: Wisp1 and The Wnt Pathwaymentioning
confidence: 99%
“…We and others have shown that air-liquid-interface (ALI) cultures of primary mouse tracheal epithelial cells can be used to evaluate the cellular and molecular mechanisms regulating FBP function (20,29,38,39,(48)(49)(50). We showed that FBP initiate ALI cultures and that K5/K15/K14 triple-positive basal cells comprise 98% of the ALI culture on Culture Day 2 (38).…”
Section: Air-liquid Interface Modelmentioning
confidence: 94%
“…We showed that FBP viability and function were not altered by transduction or recombination of a marker allele (ROSA26-floxed STOP-LacZ) (39). Interestingly, Ad5-cre transduction of FBP harboring a floxed allele resulted in generation of a mosaic epithelium that was composed of wild-type and recombined cells (38,39). This mosaicism was fortuitous, as it allowed us to study FBP behavior in genetically modified cells under identical conditions.…”
Section: Air-liquid Interface Modelmentioning
confidence: 96%
See 2 more Smart Citations